2021
DOI: 10.3390/bios11040109
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Detection of Electrolytes Using a Solid-State Ion-Selective Electrode of Single-Piece Type Membrane

Abstract: This study aimed to develop simple electrochemical electrodes for the fast detection of chloride, sodium and potassium ions in human serum. A flat thin-film gold electrode was used as the detection electrode for chloride ions; a single-piece type membrane based solid-state ion-selective electrode (ISE), which was formed by covering a flat thin-film gold electrode with a mixture of 7,7,8,8-tetracyanoquinodimethane (TCNQ) and ion-selective membrane (ISM), was developed for sodium and potassium ions detection. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…As shown in Table 1 and Table 2 , measurement range and sensitivities of DWE were comparable or superior compared with those of recently developed glucose and lactate meters. These successful measurements across a wide range of concentrations of each metabolite (0.5–35 mM for glucose and 0.5–25 mM for lactate) indicated that the proposed DEB is suitable to quantify both glucose and lactate concentrations, spanning their physiological range in mammals (0.56–35 mM for glucose and 0.5–25 mM for lactate) [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 1 and Table 2 , measurement range and sensitivities of DWE were comparable or superior compared with those of recently developed glucose and lactate meters. These successful measurements across a wide range of concentrations of each metabolite (0.5–35 mM for glucose and 0.5–25 mM for lactate) indicated that the proposed DEB is suitable to quantify both glucose and lactate concentrations, spanning their physiological range in mammals (0.56–35 mM for glucose and 0.5–25 mM for lactate) [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering this, cyclic voltammetry can further be used to establish a possible relation with the metal ion concentration based on Fenton reaction 35 . While the EIS data exhibited evidence for the correlation between impedance and metal ion/particle content, cyclic voltammetry failed to reveal solid inferences 23 . The serum standardization did not show any oxidation or reduction peaks.…”
Section: Cyclic Voltammetry Of Serum With Metalmentioning
confidence: 94%
“…Electrochemical tests that were employed are Open Circuit Potential (OCP), Electrical impedance spectroscopy (EIS), and Cyclic Voltammetry (CV). In addition, a calibration curve of current vs. concentration was generated using the cyclic voltammetry data 23 .…”
Section: Electrochemical Testsmentioning
confidence: 99%